Design, fabrication and performance evaluation of a thermoelectric cooling headgear - Abdullah Farhan Abdullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The research conducted and described in this thesis explores the design and development of a cooling system application for a helmet based on thermoelectric module (TEM) and heat sinks. The heat exchangers are designed specifically for use with this kind of cooling systems on a motorcycle helmet. Analytical and design methodology have been developed to help lay the foundations for helmet manufacturing in a professional and integrated level. As part of the characterization in this context of the research results by measuring the ability of (TEM) interacting with the heat exchanger to provide the necessary drop in temperature to Helmet environment under certain flow and constant air velocity necessary to expel the heat generated inside the helmet environment. In a related context, it has been identified the purchase list of equipment necessary to enable the possibility of the device on laboratory and practical manner. Preliminary experiments showed that the temperature measurements of the heat exchangers were within 5% of the simulation data. The potent numerical results in the selection of the appropriate available module in the markets are in a compatible and integrated manner through verification of the selection (TEM) optimized for this experiment. The temperatures were measured on the surface of the heat exchanger identical well to analytical models. Additionally, it refers to the convergence of laboratory and numerical results. Accordingly, it is an indication to the success of this research about conducted and integrated frameworks scientific basis through the achievement of the objectives of research, which can be summarized to provide a cooling system to cyclists.